Postoperative Complications and Survival Outcomes in Neonates with Congenital Diaphragmatic Hernia - RAHMAN, SHARIF UR; ZAHID, MARIA; HAROON, SALIHA; ISHTIAQ, HADIA; ISHTIAQ, NADIA; SOHAIL, IQRA; BATOOL, MARYAM; AZHAR, LAIBA; SHAKEEL, ANIQA (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Congenital diaphragmatic hernia (CDH) is a severe neonatal developmental anomaly, which is linked to pulmonary hypoplasia, persistent pulmonary hypertension, respiratory failure, and is a major cause of morbidity and mortality in the immediate postoperative period. Efforts to improve the survival of infants with surgical repair of congenital heart defects have continued but still have detrimental effects on outcome, especially in less developed health care systems, because of postoperative complications. Objective: To assess the complications and survival rates of neonates who are surgically repaired for congenital diaphragmatic hernia. Methods: This prospective observational study was conducted at the Departments of Pediatric Surgery and Neonatal Intensive Care Units of Rashid Latif Medical College/RIHS and Nishtar Medical University, Pakistan, from June 2024 to June 2025. A total of 80 neonates diagnosed with congenital diaphragmatic hernia who underwent surgical repair were enrolled through non-probability consecutive sampling. Demographic data, peri- and postoperative data, and outcome measures were collected and analyzed with SPSS 26.0. A p-value <0.05 was considered statistically significant. Results: Among 80 neonates, 47 (58.8%) were males and 33 (41.2%) were females. Sixty-one (76.3%) neonates had left-sided CDH, and 21 (26.3%) neonates had liver herniation. Thirty-eight (47.5%) neonates had postoperative complications. The most prevalent complication was found in 16 (20.0%) neonates, persistent pulmonary hypertension, followed by respiratory failure in 12 (15.0%) and pneumothorax in 9 (11.3%) patients. The average mechanical ventilator duration in our patients was 8.9 ± 4.6 days and the average NICU stay was 18.7 ± 8.4 days. Overall survival to discharge was 57 (71.3%) and the remaining 23 neonates (28.7%) died in hospital. Prematurity, low birth weight, liver herniation, PHTN and long periods of ventilator support were significantly associated with mortality (p<0.05). Conclusion: Surgical repair of congenital diaphragmatic hernia is associated with a high incidence of post-operative complications that affect neonatal survival. In order to achieve better postoperative outcomes and mortality in affected neonates, prompt management of pulmonary and infectious complications, early diagnosis, and aggressive periopertative stabilization and optimized ventilatory support are paramount.